Relationship between critical thinking and creative thinking through zoom meeting on science learning in elementary school - Faradita, Meirza Nanda; Adi Putra, Deni; Nuruddin, Muhammad (Universitas Nusantara PGRI Kediri, 2022)
Humans are social creatures who need to develop themselves in facing life in society. To understand something, a person's way of thinking is influenced by knowledge, the ability to see, and the ability to create a strategy in thinking. One of them is in the education. Based on observations, it is shown that the learning carried out by the teacher when teaching is less varied so that it seems monotonous and the questions asked by the teacher are not in-depth only in the cognitive domains of C1 and C2. Lack of direct application (practice) when learning and the work made by students is less innovative. Through the zoom application, students can also do online learning. This study aims to determine the relationship between students' critical and creative thinking through the Zoom application and science learning outcomes. The type of research used in this research is quantitative correlational type. The subjects of this study were fifth grade students of SD Muhammadiyah 8 Surabaya. From the research that has been carried out, the results obtained are: (1) There is a relationship between critical thinking through the Zoom application and science learning outcomes, because the value of Sig. < 0.05 (0.008 < 0.05); (2) There is a relationship between creative thinking through the Zoom application and science learning outcomes, because the value of Sig. < 0.05 (0.006 < 0.05); (3) There is a relationship between critical and creative thinking through the Zoom application with science learning outcomes because of the value of Sig. < 0.05 (0.009 < 0.05)